RESPECT THE NON INTERVENTION, DISRESPECT THE HUMANITY - Humairoh, Uum (Journal of Islamic Law Studies, 2018)
The non-intervention means that the equal sovereign states shall not intervene in each other’s internal affairs. The non-intervention would be regarded as an equivalent of non-intervention. The countries have obligation to obey this term to avoid other country’s intervention. Sometimes, it brings positive impact to the country, meaning that the country can stand alone to handle any issues, internal or external. However, as the time goes by, this issue of non-intervention has become debatable. ASEAN, regional organization in South East Asian, has used this term as basic prin- ciple to run the organizational function. ASEAN cannot be involved in the country members’ business. It will be different if the organization is encountered with human right issue. This paper will discuss how this basic principle of ASEAN faces various conflicts. This principle has made ASEAN not to be able to take any action regarding the human rights issue. The human violence suffered by Rohingya society in Myanmar has become challenge which must be solved together. ASEAN, as the supreme organization in South East Asian, is expected to find solutions for this issue.